Benefit of continuous kidney replacement therapy for managing tumor lysis syndrome in children with hematologic malignancies - Anderson, Ashlea; Shoulders, Laurie; James, Vinson; Ashcraft, Emily; Cheng, Cheng; Ribeiro, Raul; Elbahlawan, Lama (Frontiers in Oncology, 2023)
Introduction Tumor lysis syndrome (TLS) is often diagnosed in children with hematological malignancies and can be life threatening due to metabolic disturbances. Continuous renal replacement therapy (CKRT) can reverse these disturbances relatively quickly when conventional medical management fails. Our objective was to investigate the benefit of CKRT in the management of TLS in children admitted to the intensive care unit with hematologic malignancies. In addition, we sought to assess risk factors for acute kidney injury (AKI) in the setting of TLS. Methods Retrospective review of all children admitted to the intensive care unit with TLS who received CKRT from January 2012 to August 2022. Results Among 222 children hospitalized with TLS from January 2012 to August 2022, 20 (9%) underwent CKRT to manage TLS in the intensive care unit. The patients’ median age was 13 years (range 3-17 y), and most were males (18/20). T-cell acute lymphoblastic leukemia was the most common diagnosis (n=10), followed by acute myeloid leukemia (n=4), Burkitt lymphoma (n=4), and B-cell acute lymphoblastic leukemia (n=2). Five patients required mechanical ventilation, and 2 required vasopressors. The most common indication for CKRT was hyperphosphatemia, followed by, hyperuricemia, and hyperkalemia. All metabolic abnormalities corrected within 12 h of initiation of CKRT. CKRT courses were brief, with a median duration of 2 days (range 1-7 days). Having higher serum phosphorus levels 12 h preceding CKRT was significantly associated with severe acute kidney injury (AKI). The median phosphorus level was 6.4 mg/dL in children with no/mild AKI and 10.5 mg/dL in children with severe AKI (p=0.0375). Serum uric acid levels before CKRT were not associated with AKI. All children survived to hospital discharge, and the one-year survival rate was 90%. Conclusion CKRT is safe in children with hematologic malignancies with severe TLS and reverses metabolic derangements within 6-12 h. Most patients had AKI at the initiation of CKRT but did not require long-term kidney replacement therapy. Hyperphosphatemia before initiation of CKRT is associated with higher risk of AKI.